Effect of atmospheric‐controlled induction‐heating fine particle peening on microstructure and fatigue properties of low‐alloy steel. Issue 10 (10th July 2022) - Takesue, Shogo; Hayama, Motoaki; Komotori, Jun
Abstract: Atmospheric‐controlled induction‐heating fine particle peening (AIH‐FPP) was performed for low‐alloy steel, and the effects of the peening temperature, the microstructure of steel, and thermal history during AIH‐FPP on the resultant microstructure of treated steel were investigated. Regardless of the prior microstructure and thermal history, the grains near the surfaces were refined by AIH‐FPP at peening temperatures from 923 K to 1023 K owing to dynamic recrystallization. To examine the effect of AIH‐FPP on the fatigue properties of steel, plane‐bending fatigue tests were performed. Compared with the steel mirror‐polished, treated with FPP at RT, or only induction‐heated, the fatigue properties of steel treated with AIH‐FPP were improved. This is because of the formation of a thick and uniform grain‐refined layer, the generation of compressive residual stress, and hardening of the surface by AIH‐FPP. Moreover, owing to the grain refinement progress, the fatigue properties of steel improved with increasing peening temperature. Highlights: AIH‐FPP can refine grains regardless of prior microstructure of steel and thermal history. AIH‐FPP can improve fatigue properties of low‐alloy steel AISI4140. The fatigue properties improved with the increasing peening temperature during AIH‐FPP. AIH‐FPP is more effective at improving the fatigue properties than FPP at RT or only IH.